Financial Health Management and Its Impact on Company Employee Welfare: Case Study in the Manufacturing Industry - Rosid, Abdul; Sundari, Retno; Sofyan, Hady; Hartoto, Hartoto (International Journal of Economics (IJEC), 2024)
This study explores the relationship between financial health management and employee well-being in the petrochemical and chemical industries. Using a case study method and a mixed-methods approach, the study analyzes how effective financial management affects various aspects of employee well-being, including job satisfaction, mental health, and personal financial stability. Quantitative data were obtained from a survey measuring the relationship between financial management practices and employee well-being, while qualitative data were obtained through in-depth interviews with financial managers, HR managers, and employees. The findings indicate that companies with good financial management tend to have more satisfied, mentally healthy, and financially stable employees. In addition, transparent and participatory financial management improves corporate culture and the relationship between management and employees. This study emphasizes the importance of integrating good financial practices and employee well-being policies in creating a productive and harmonious work environment.